A novel approach to assessing precarious rock instability in high-cold regions considering freeze-thaw forces - Zhao, Yonghui; Hu, Kun; Han, Deming; Lang, Yongxian; Zhang, Lin (Frontiers in Earth Science, 2024)
In high-cold regions, the instability of precarious rock masses in open-pit mines is often exacerbated by the effects of freeze-thaw cycles, posing a significant threat to the continuous production of open-pit mining operations. To address this issue effectively, we conducted an in-depth study on the precarious rock masses in the near-slope of a mining area in a high-cold region using a fracture mechanics-based stability analysis method. We analyzed the impact of freeze-thaw cycles on the engineering stability. Introducing a novel approach, we established the temperature field at different time points to determine whether the freeze-thaw depth influences the generation of freeze-thaw forces on the controlling structural surfaces. Employing the maximum circumferential stress criterion, we conducted a comprehensive analysis of tension cracks in the slope and derived corresponding safety factor expressions. Focusing on retrogressive rock slopes, we divided the slope's precarious rock masses into n potentially unstable approximate rectangular rock bodies. Based on this, we developed a fracture mechanics-based slope stability calculation method considering the combined effects of freeze-thaw forces, crack water pressure, and gravity. Through relevant numerical examples, we successfully calculated the safety factors of the segmented rock bodies, revealing the varying influence of freeze-thaw forces on rock mass stability. By integrating the calculation results with practical engineering considerations, we validated the feasibility of our proposed method. Lastly, aligning with pertinent precarious rock stability assessment criteria, we provided corresponding remediation measures based on the distinct stability conditions of the rock masses. Through comprehensive research and an effective computational approach, we offer a scientifically viable solution for the stability of precarious rock masses in open-pit mines in high-cold regions, thereby providing robust technical support for the sustainable production of mining enterprises.